The antioxidant activity of several antidiabetic herbal products - Ichwan Ridwan Rais; Andhika Septiawan; Meta Ayuni; Dhega Agung Wichaksono; Nanik Sulistyani (Pharmaciana, 2022)
The oxidative stress mechanism in the body involves the balance between increased ROS and decreased antioxidant agents. ROS can damage DNA, proteins, and lipids, leading to pathology and impaired insulin secretion by dysregulation of several genes expression. High concentrations of ROS are often followed by a low activity of antioxidants from endogenous sources. As a result, exogenous antioxidants are required to neutralize ROS. As reported, medicinal plants, which have had various traditional applications, contain large amounts of secondary metabolites, proven to be exogenous antioxidant agents. Jamu, a traditional medicine, also known as an alternative medication, can be widely and easily found in traditional markets. Antidiabetic herbal products are among the most popular of jamu. Antidiabetic mechanism has a strong relationship with antioxidant roles in many biological systems. The aim of this research was to figure out the potential antioxidant activity of antidiabetic herbal products. Eight antidiabetic jamu samples were analyzed for their antioxidant activity by measuring the DPPH radical scavenging activity, phosphomolybdenum antioxidant activity, and FRAP, as well as for their total phenolic and flavonoid contents. Good linearity was a general finding for the quantitative analysis, with an average correlation coefficient of 0.999 for the standards. The highest total flavonoid content found was 8.66 ± 0.11 mgQE/g, and the highest total phenolic content was 22.66 ± 0.15 mgGAE/g. With regard to antioxidant activity, all of the samples demonstrated weak DPPH radical scavenging activity, while phosphomolybdenum antioxidant activity and FRAP were the highest at 48.58 ± 0.45 mgQE/g extract and 226.98 ± 0.19 mgQE/g extract, respectively. These results indicated that the claimed antidiabetic herbal products could be prepared as exogenous antioxidant sources, irrespective of being with or without antioxidant activity, for diabetes treatment.